The Paradox of Salvation : Luke's Theology of the Cross - Doble, Peter; General Editor of Series : Margaret E. Thrall (Cambridge ; New York Cambridge University Press, 1996)
Refuting the allegation that the author of Luke-Acts showed no systematic thought about the significance of Jesus' death, this study affirms that Luke had a coherent theologia crucis. Peter Doble focuses sharply on the Gospel's death scene and explores three features which appear in Luke alone, then extends the exploration into the longer account of Jesus' final days in Jerusalem.
Include Index
Keywords: Theology -- Crucifixion--Biblical Teaching -- Jesus Christ